A new species of Pseudovaigamus Amado, Ho & Rocha, 1984 (Cyclopoida: Ergasilidae) from the teleost Pimelodus maculatus Lacepède, 1803 - NARCISO, RODRIGO B. [UNESP]; PERBICHE-NEVES, GILMAR; DA SILVA, REINALDO JOSÉ [UNESP] (Magnolia Press, 2020)
A new species of the copepod genus Pseudovaigamus Amado, Ho & Rocha, 1984 is described herein based on parasitic adult females found attached to the gills of the freshwater teleost Pimelodus maculatus Lacepède, 1803, sampled in two tributaries (Veados and Paranapananema Rivers) of the Jurumirim Reservoir, Upper Paranapanema River, São Paulo State, Brazil. The new copepod was identified as an undescribed species of Pseudovaigamus because it shares with the type-species, Pseudovaigamus spinicephalus (Thatcher & Robertson, 1984), the combination of first leg with 2-segmented endopod, fourth leg with 3-segmented endopod and 2-segmented exopod, and cephalothorax armed with dorsolateral stylets (or retrostylets). However, the new copepod differs from its congener in having a trifid rostral spine, retrostylets with long spatulate process, 5-segmented antennule, and caudal rami simple or lacking any distal lobe. We erected a new species, Pseudovaigamus tridentatus n. sp. It is the first report of a Pseudovaigamus found on a freshwater fish in Brazil.
Keywords: Crustacea; Freshwater; Jurumirim Reservoir; Neotropical region; Paranapanema River; Parasitic copepods; Taxonomy